Authentic Assessment Practices In Digital Science Classrooms: A Review of Strategies and Barriers - Baiq Nabila Saufika Zainuri; Gunawan Gunawan; Qothrunnada Qothrunnada (Indonesian Journal of Applied Science and Technology, 2025)
The development of digital learning demands the implementation of assessments that can authentically and contextually measure students' competencies, particularly in science education. This research aims to examine the types of authentic assessment, the digital platforms used, and the obstacles and challenges of its implementation in digital science learning. The method used is a systematic literature review of scientific articles published between 2015 and 2024 that are relevant to the topic of authentic assessment and digital learning. The study results indicate that authentic assessment in digital science learning is dominated by project-based assessment, performance assessment, and digital portfolios supported by a learning management system, virtual laboratories, and e-portfolios. Although authentic assessment has proven capable of increasing student engagement and higher-order thinking skills, its implementation still faces pedagogical, technological, and institutional challenges. These findings confirm the need to strengthen teacher competencies, infrastructure support, and assessment policies that are adaptable to digital learning.